Improvement of PMMA Dental Matrix Performance by Addition of Titanium Dioxide Nanoparticles and Clay Nanotubes - Mariafrancesca Cascione; Valeria De Matteis; Paolo Pellegrino; Giovanni Albanese; Maria Luisa De Giorgi; Fabio Paladini; Massimo Corsalini; Rosaria Rinaldi (Nanomaterials, 2021)
Over the last decades, several materials have been proposed for the fabrication of dental and mandibular prosthetic implants. Today, the poly(methyl-methacrylate) (PMMA) resin is the most spread material, due to its ease of processing, low cost, aesthetic properties, low weight, biocompatibility, and biostability in the oral cavity. However, the porous surface (which favors the adhesion of microorganisms) and the weak mechanical properties (which lead to wear or fracture) are the major concerns. The inclusion of engineered nanomaterials in the acrylic matrix could improve the performances of PMMA. In this study, we added two different kind of nanomaterials, namely titanium dioxide nanoparticles (TiO2NPs) and halloysite clay nanotubes (HNTs) at two concentrations (1% and 3% w/w) in PMMA. Then, we assessed the effect of nanomaterials inclusion by the evaluation of specific physical parameters: Young’s modulus, roughness, and wettability. In addition, we investigated the potential beneficial effects regarding the Candida albicans (C. albicans) colonization reduction, the most common yeast responsible of several infections in oral cavity. Our experimental results showed an improvement of PMMA performance, following the addition of TiO2NPs and HNTs, in a dose dependent manner. In particular, the presence of TiO2NPs in the methacrylate matrix induced a greater increase in PMMA stiffness respect to HNTs addition. On the other hand, HNTs reduced the rate of C. albicans colonization more significantly than TiO2NPs. The results obtained are of great interest for the improvement of PMMA physico-chemical properties, in view of its possible application in clinical dentistry.